2017
DOI: 10.1039/c6cp08149e
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation clusters in lipid systems – surface effects, local heating and streamer formation

Abstract: Cavitation clusters and streamers are characterised in lipid materials (specifically sunflower oil) and compared to water systems. The lipid systems, which are important in food processing, are studied with high-speed camera imaging, laser scattering and pressure measurements. In these oils, clusters formed at an aged (roughened) tip of the sound source (a piston like emitter, PLE) are shown to collapse with varied periodicity in relation to the drive amplitude employed. A distinct streamer (an area of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…7. These results showed that the number of subharmonics generated during sonication were not affected by the temperature of the samples and that the number of subharmonics is only dependent on the power level employed as previously shown by Birkin et al (2017, 2019). Fig.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…7. These results showed that the number of subharmonics generated during sonication were not affected by the temperature of the samples and that the number of subharmonics is only dependent on the power level employed as previously shown by Birkin et al (2017, 2019). Fig.…”
Section: Resultssupporting
confidence: 82%
“…This was recorded by an in-house program (Visual Studio 2010, including Measurement Studio 2012 and USB-204 DAQ card [National Instruments]). A detailed description of the experimental setup can be found in Birkin et al (2017Birkin et al ( , 2019.…”
Section: Cavitationmentioning
confidence: 99%
See 3 more Smart Citations